Pengaruh Metode Ekstraksi Terhadap Kandungan Flavonoid dan Efektivitas Antibakteri Hand Sanitizer Dari Kulit Jeruk (Citrus Sinensis L.) - Aisyah, Widya; Sinardi, Sinardi (UIR Press, 2025)
Sweet orange peel (Citrus sinensis L.) is an agricultural by-product with promising potential as a natural raw material for hand sanitizer due to its bioactive compounds, particularly flavonoids, known for their antibacterial properties. This study investigates the influence of two extraction methods—infusion and maceration—using peel weights ranging from 10–50 g, on the characteristics and quality of hand sanitizer formulations. The products were evaluated through pH, density, drying time, organoleptic properties, skin irritation, flavonoid identification, and antibacterial activity against Escherichia coli using the disc diffusion method. Results showed that maceration yielded a more intense brick-red color at 40 g and 50 g, while infusion produced only a concentrated yellow extract. All formulations exhibited pH values within the safe skin range (4.5–6.5), density of 0.86–0.90 g/mL, and drying times of 14–22 seconds. No irritation was observed in skin tests, and panelist acceptance was higher in formulations containing 30–50 g peel. However, none of the hand sanitizer formulations inhibited E. coli growth (0 mm), in contrast to the positive control (Ciprofloxacin 100 ppm), which produced a 31.55 mm inhibition zone. The lack of activity is likely due to the Gram-negative nature of E. coli, low flavonoid concentrations, limited gel diffusion, and compound degradation.